Driving green digital innovation in higher education: the influence of leadership and dynamic capabilities on cultivating a green digital mindset and knowledge sharing for sustainable practices - Yifei Shen; Yong Deng; Zhonghua Xiao; Zhiwu Zhang; Rui Dai (BMC Psychology)
Abstract Purpose The new generation loves to interact with digital technologies. On the other hand, due to the soaring digital innovation trends, sustainability is crucial in higher educational institutes (HEI), necessitating investigating the factors that lead to green innovations. Therefore, drawing on the Stimulus-organism-response approach (SOR) and dynamic capability view, the current study examines the intricate relationship between digital leadership, dynamic capability, knowledge sharing, green digital mindset and green digital innovation in higher education settings. Methods This research utilized the three-wave (T1 = digital leadership, dynamic capability, T2 knowledge sharing, green digital mindset, T3 = green digital innovation) research approach to collect the data in a one-month time lag from the top management of universities working in China. At T3, 425 filled questionnaires were received, which were utilized for the final data analysis. SmartPLS 4.0 was employed for data analysis. Results The results present mixed findings, as digital leadership was an insignificant predictor of green digital innovation. However, Dynamic capability and knowledge sharing underscore the crucial role of both as predictors to foster green digital innovation in Chinese universities. Furthermore, the study reveals the significant mediating role of knowledge sharing between digital leadership, dynamic capability and green digital innovation. Conclusion This study postulates that knowledge sharing and green digital innovation will be stronger in the presence of a green digital mindset in Higher education institutions. HEIs should ensure a dynamic culture that adapts technology and sustainability principles to remain at the forefront of digital and green innovation.